Reconstitution of trimethylamine-dependent coenzyme M methylation with the trimethylamine corrinoid protein and the isozymes of methyltransferase II from Methanosarcina barkeri. - Ferguson, D J (1997)
Reconstitution of trimethylamine-dependent coenzyme M (CoM) methylation was achieved with three purified polypeptides. Two of these polypeptides copurified as a trimethylamine methyl transfer (TMA-MT) activity detected by stimulation of the TMA:CoM methyl transfer reaction in cell extracts. The purified TMA-MT fraction stimulated the rate of methyl-CoM formation sevenfold, up to 1.7 micromol/min/mg of TMA-MT protein. The TMA-MT polypeptides had molecular masses of 52 and 26 kDa. Gel permeation of the TMA-MT fraction demonstrated that the 52-kDa polypeptide eluted with an apparent molecular mass of 280 kDa. The 26-kDa protein eluted primarily as a monomer, but some 26-kDa polypeptides also eluted with the 280-kDa peak, indicating that the two proteins weakly associate. The two polypeptides could be completely separated using gel permeation in the presence of sodium dodecyl sulfate. The corrinoid remained associated with the 26-kDa polypeptide at a molar ratio of 1.1 corrin/26-kDa polypeptide. This polypeptide was therefore designated the TMA corrinoid protein, or TCP. The TMA-MT polypeptides, when supplemented with purified methylcorrinoid:CoM methyltransferase (MT2), could effect the demethylation of TMA with the subsequent methylation of CoM and the production of dimethylamine at specific activities of up to 600 nmol/min/mg of TMA-MT protein. Neither dimethylamine nor monomethylamine served as the substrate, and the activity required Ti(III) citrate and methyl viologen. TMA-MT could interact with either isozyme of MT2 but had the greatest affinity for the A isozyme. These results suggest that TCP is uniquely involved in TMA-dependent methanogenesis, that this corrinoid protein is methylated by the substrate and demethylated by either isozyme of MT2, and that the predominant isozyme of MT2 found in TMA-grown cells is the favored participant in the TMA:CoM methyl transfer reaction.